Spirit riding free. Lucky and the mustangs of Miradero - Selfors, Suzanne (Spirit riding free, 2017)
Lucky Prescott and Spirit, the wild stallion, have an unbreakable bond. Along with their new best friends, Abigail and Pru, Lucky and Spirit set off on daring adventures, push their limits, and discover what it means to be truly free.